Software architecture: from modelling to automated validation within Bosch Thermotechnology - Lajoso, João Pedro da Silva (2021)
Surrounded by technology daily, we no longer need to think to interact with the various services and products that are already designed to adapt directly to Man: this is the modern way of life in a more digital society. In this report, we intend to explore the methods for a multinational to provide us with the most varied products for different market segments, maintaining high levels and quality standards. The focus of Bosch Thermotechnology is oriented towards residential water heating products and services. However, concerning software and methodologies, there is a sharing between the entire Bosch group community, which leads to a continuous search for solutions. The problem of having many software teams with different backgrounds implies an extensive set of tools and programming languages, so in the first phase, it was essential to map the teams in order to have a general image of the tools; then, the tools for automation were explored, from the project creation and modelling process to the maturity and complexity of large projects. As a method for analyzing the internship results, it was necessary to divide it into different parts: Status-Quo, Market Tools Appraisal research, and finally Proof-of-Concept. The expected contribution to this area is that of a solution that integrates people, data flows, and processes, which will leverage efficiency gains in the daily tasks of architects, in decision-making processes, and in the identification and elimination of non-value activities, thus improving the overall performance of planning.